Evaluation of HIV-1 drug resistance among patients failing first-line antiretroviral therapy in Ethiopia. (September 2022) - Getaneh, Yimam; He, Qianxin; Rashid, Abdur; Kassa, Desta; kang, Li; Yi, Feng; Liao, Lingjie; Shao, Yiming
Highlights: A total of 9433 PLHIV taking antiretroviral therapy were selected from 63 facilities in Ethiopia. There is high HIV-RTI resistance (77.8%) among people failing first-line treatment. Prior HAART exposure and disclosure status were predictors for HIV drug resistance. Bedridden and immunosuppressed were independent clinical predictors for HIV drug resistance. The program shall consider drugs targeting protease and integrase. ABSTRACT: Objectives: The aim of this study was to evaluate HIV-1 drug resistance among patients failing first-line antiretroviral therapy in Ethiopia. Methods: A total of 699 adults infected with HIV (aged ≥15 years) who failed first-line Antiretroviral Therapy (ART) were recruited between 2017 and 2019 from 63 ART-providing sites in Ethiopia. Treatment failure was defined as patients with two consecutive viral loads (VLs) ≥1000 copies/mL within six months of follow-up. The pol gene region of HIV-1 was amplified and sequenced using an in-house assay of the Chinese Center for Disease Prevention and Control. The Stanford HIVDB v9.0 algorithm was used for identification of resistance mutations. Resistance mutations were characterized according to the 2019 International AIDS Society-USA mutation list. P values of <0.05 were considered statistically significant during multivariate analysis, which was done using SPSS v26.0 (SPSS Inc., Chicago, IL). Results: Overall, HIV drug resistance (HIVDR) among patients failing first-line therapy in Ethiopia was 77.8%. Non-nucleoside/tide reverse transcriptase inhibitors (NNRTI) and NRTI resistance were 75.7% and 71.2%, respectively. Neverapine (NVP) and Efavirenz (EFV) accounted for 74.2% and 60.8% of HIVDR, respectively. About half (48.1%) of NRTI-associated mutations were responsible for Abacavir resistance, while 34% were responsible for multi-NRTI resistance. Mutations responsible for resistance to the commonly used EFV and NVP accounted for 62.9%, while resistance to Etravirine, Doravirine, and Rilivirine, which were not part of the country's ART program, were 37.1%, and can be explained by cross-resistance within the drug class. Protease Inhebitor(PI)associated resistance was detected in only 1.6% of the study's participants. The most common mutations identified were M184V (30.1%), K103N (18.7%), Y181C (13.6%), and K65R (12.1%). In a multivariate logistic regression analysis, predictors of HIVDR were prior ART exposure (adjusted odds ratio [AOR] = 2.3; 95% confidence interval [CI] = 1.8, 3.6), absence of HIV status disclosure (AOR=2.05; 95%CI=1.26, 3.35), CD4 count of ≤200 cells/mm 3 (AOR=1.94; 95%CI=1.21, 3.12), and bedridden status (AOR = 4.16; 95% CI = 3.21, 5.16). Conclusion: The high-levels of HIVDR among patients with failure of first-line ART in Ethiopia calls for individualized HIVDR testing. Mutations associated with multi-NRTI and NNRTI cross-resistance may alert the program for considering drugs of higher genetic barrier targeting protease and other regions. Patients with low CD4 count and those who are bedridden should be given special attention for the potential development of HIVDR during clinical management.